Representation of Female Trauma and Voice in Khakhpour‟s Sick: A Memoir - Abbas, Ghulam (International Journal of Psychosocial Rehabilitation, 2020)
Abstract--- Present study aims to illustrate the issue of female trauma and voice in the light of novel Sick: A Memoir by Porochista Khakpour. This study claims that there are some other issues in this novel as well and to lemmatize this novel merely as a memoir is wrong. The novel presents social issues how the females are considered in the male oriented society and how they are constructed. The identity of the females is exploited by the males. This novel has been presented by a female writer who belongs to Iran and who spent a great deal of her life as a sick woman and bore the jolts of life. She has also spent a great deal of money to cure the disease named as Lyme. Since this was the diseases related to the women so it was not dealt by the researchers conveniently. The novel presents a situation that is very grim in nature and depicts a grueling story of womanhood. It shows that most of the trauma that is with the females is created by the men and society. Both of them lemmatize the women merely to the four walls of their houses and the women cannot deny from this social action that is against them. The mental agonies which are faced by the women are very strict that deteriorate the health of the females. On the other hand, the novel also shows that there are gaps in the medical system of the world due to which people meet their eternal world. This novel is the story of the pain afflicted to the women due to being of woman. On the other hand the social, psychological, emotional impacts of this disease have been dealt in this study.